THE RELATIONSHIP BETWEEN EARLY ABILITY, LEARNING MOTIVATION AND LEARNING HABITS WITH MATHEMATICS LEARNING OUTCOMES IN STUDENTS CLASS X - Nadhif Nur Kholifah; Edi Prajitno (Universitas Ahmad Dahlan, 2018)
Low student learning outcomes associated with many factors. The relationship between Early Ability, Learning Motivation, and Learning Habits is allegedly related to learning outcomes. This research aims to determine the presence or absence of positive and significant the relationship between Early Ability, Learning Motivation, and Learning Habits with Mathematics Learning Outcomes in Students Class X MIA in Odd Semester of SMA Muhammadiyah 5 Yogyakarta in Academic Year of 2017/2018. The population in this research was the students of class X MIA in odd semester of SMA Muhammadiyah 5 Yogyakarta in the academic year of 2017/2018, consisted of class X MIA 1, X MIA 2 totaling 60 students. While research samples are one class, i.e., class X MIA 1 was taken by a random sampling technique to the class. Technique data collection using the questionnaire method and test method. The research instrument use validity test, different power, and reliability test. Test requirement analysis includes a test of normality, a test of independence, and a linearity test. The writer uses linear regression analysis and correlation analysis. The results showed that there was a positive and significant relationship between early ability, learning motivation, and learning habits with mathematics learning outcomes in students class X MIA in Odd Semester of SMA Muhammadiyah 5 Yogyakarta in Academic Year of 2017/2018. It is showed by is and 2,98 with Coefficient of multiple correlation ( ) amount 0,880 and coefficient determination double amount 0,332 with the linear regression equation . 38,048%, and and and .